2015
DOI: 10.1007/s10008-015-2887-7
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of water vapor on the Li–O2 battery using a solid-state air cathode

Abstract: A lithium (Li)-oxygen (O 2 ) battery based on an inorganic solid-state air cathode was fabricated, and the influence of water vapor (key component in the air) on the electrochemical behavior of the proposed Li-O 2 battery was deeply investigated. Excluding the negative influence of the corrosion of Li anode that existed in organic-based electrolyte Li-O 2 battery when operated in wet environment, our results showed that water vapor has a positive effect on the discharge and cycling performances of the Li-O 2 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
(59 reference statements)
0
25
0
Order By: Relevance
“…Solid-state electrolyte avoids the evaporation of organic liquid solvent. [214][215][216][217] They show no permeability of humidity and CO 2 , and thus prevent direct reaction between the Li anode and H 2 O/CO 2 in air. The LATP and LAGP based Li-ion conductive membranes studied initially were in direct contact with the anode and cathode, which causes large interfacial charge transfer resistance.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Solid-state electrolyte avoids the evaporation of organic liquid solvent. [214][215][216][217] They show no permeability of humidity and CO 2 , and thus prevent direct reaction between the Li anode and H 2 O/CO 2 in air. The LATP and LAGP based Li-ion conductive membranes studied initially were in direct contact with the anode and cathode, which causes large interfacial charge transfer resistance.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…In efforts to isolate water vapors influence on the three phase interface, Wang et al conducted control experiments utilizing a solid-state air cathode, to mitigate potential water dissolution into the electrolyte. [17] The discharge/charge curves showed that the discharge voltage in wet O 2 (2.66 V) is slightly higher than that in dry O 2 (2.55 V) but with nearly the same specific capacity (Figure 1c). Meanwhile, once the external atmosphere altered to wet O 2 , the characteristic peaks corresponding to LiOH could be observed clearly in the discharge product based on the XRD characterization, indicating that the existence of water vapor led to the formation of LiOH via side reaction (Figure 1d and e).…”
Section: Water Contamination In Omentioning
confidence: 92%
“…[16] Copyright 2012, The Electrochemical Society. (c) Discharge/charge curves of the 17 (f) The titration is conducted on Ru/SP in different electrolytes in the discharging processes. Reproduced with permission.…”
Section: Water Contamination In Omentioning
confidence: 99%
“…In particular, a water impurity is a nonnegligible factor, which could affect the electrochemical performance of practical non-aqueous LABs or LOBs tremendously. Previous reports have demonstrated that the presence of water from humidity or in the electrolyte will change the electrochemical process and enhance the discharge capacity via the formation of toroidal or plate-shaped discharge products on the air electrode through a solution-based mechanism. In Zhu’s work, the fraction of platelike LiOH in the discharge products increases with relative humidity and LiOH further changes to a film-like morphology at high humidity. The appearance of LiOH leads to a higher discharge voltage and a lower charge voltage of the Li air battery with a 1 M LiTFSI/TEGDME electrolyte than that working in a dry atmophere .…”
mentioning
confidence: 92%